A Making Monologue To Improve Students’ Writing Skill - Wiggy Ramadhani; Abdul Rohman; Widi Syahtia Pane (Inquest Journal, 2023)
Life is requiring some skills in order to improve society’ integrity and some people may have distinct skills. In every aspect of life one of the most important skill in life is writing. Writing skill is a part of skill in life in order to work. So the author wanted to do a research towards writing skill in high school students by making monologue. The study was conducted by taking samples from students in SMA NEGERI 5 SAMARINDA, this study aims to see how the efficacy of making monologue in order to improve students’ writing skill, basically making monologue is a long speech given by a character in a story, movie, play, etc., and in the end, the results show making monologue is significant to improve students’ writing skill.The researcher used Classroom Action Research (CAR) for the methodology and used 2 cycles and 5 meetings in SMA NEGERI 5 SAMARINDA and 11 Science 1’s Students as subjects. The researcher found In the last meeting of the last cycle that there were 89% of students who were successful